Giving Dfferent Natural Foods To Growth, Survival Rate and Brightness of Neon Tetra Fish ( Paracheirodon innesi ) - Yunita Yunita; Usman M Tang; Niken Ayu Pamukas (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACTThis study aims to determine the best types of natural food for growth performance, survival rate and color brightness of neon tetra fish (Paracheirodon innesi). The method of this research was using the experimental method with Completely Randomized Design (RAL) by using one factor of 4 treatment levels and 4 replications. The tratments were using pellet (control), Tubifex sp, Moina sp and Bloodwarm. The fry size was around 1.2-1.5 cm and weight was 0.065 gthen reared in the aquarium by 15 L of water and 15 fishes of stocking density each aquarium. The fish were reared for 40 days and feed is given as much as 10% of biomass weight, e times a day of feeding frequency. The results showed that the best treatment was Tubifex sp by giving absolute weight growth for 0.14 g, absolute longevity for 0.58 cm, specific growth rate for 2.99% and fish survival for 98%, while the best color brightness by giving a Bloodwarm. The conclusion is different types of natural diets significantly affect the growth performance, survival rate and color brightness of neon tetra fish (Paracheirodon innesi).Keywords: Natural food; Growth; Survival rate; Color brightness; Neon tetra; Paracheirodon innesi.